The Effect of E-Module TRIAD Kesehatan Reproduksi Remaja (KRR) on HIV Self-Efficacy in Preventing HIV Vulnerable Behaviour - Wilandika, Angga; Kamila, Ami; Sofiyah, Yusi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2021)
HIV infection is one of the three threats to reproductive health in adolescents (TRIAD Kesehatan Reproduksi Remaja). In order to reduce this risk to adolescents, a strategy is needed to prevent this problem by providing education through electronic modules or e-modules. Education with e-modules is expected to increase adolescent self-efficacy in preventing HIV risk behaviour. This study purpose was to determine the effect of education through e-module on changes in self-efficacy to prevent HIV risk behaviour in adolescents. This quantitative study used a single group pretest-posttest research design. The sample in this study were VIII grade junior high school students at one of the private schools in Bandung Regency which consisted of several classes by providing education using e-modules. There were 40 students involved in this research. The intervention given to students was education about the dangers of HIV and risk behaviours using E-Module of TRIAD Kesehatan Reproduksi Remaja. Meanwhile, the instrument used in the study was the self-efficacy assessment instrument for the prevention of HIV-risk behaviour. The results of the study found that there was a change in the scores of self-efficacy in the prevention of HIV risk behaviour in students, before and after education through e-modules. Therefore, it can be concluded that e-module is effective in increasing adolescent self-efficacy. The results of this study become recommendations for academics and practitioners who are involved in the health sector for adolescents to implement an intervention to prevent risky behaviours that threaten adolescents, especially in relation to HIV/AIDS problems.